Implementasi Teknologi Informasi Dan Komunikasi Dalam Manajemen Organisasi Pendidikan - Nisa Aldira Lubis; Putri Fadila Ramadhani; Dandi Salmanda; Fadlan Fadlan; Ahmad Mukhlasin (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2024)
The utilization of information and communication technology (ICT) in the management of educational institutions has become a key element of improving operational efficiency and effectiveness in the digital era. This study aims to investigate the role of ICT in data management, management, learning processes, and communication in educational environments. Using literature review techniques and secondary data analysis, this study found that the use of ICT increases information transparency, accuracy and speed, improving resource management and decision-making. However, ICT implementation also faces many challenges, such as infrastructure limitations, lack of technical capacity of human resources, and resistance to change. Overcoming these barriers requires a comprehensive and sustainable strategy. The results of this study are expected to provide insights to stakeholders in education regarding better management and optimization of ICT utilization to achieve quality education.unik.